Analysis of Teaching Materials and Learning Methods for the Professionalism and Leadership Course in the Implementation of Religious Moderation in Islamic Early Chilhood Education Study Program, State Islamic University Sunan Kalijaga Yogyakarta - Pangestuti, Puji; Nadlifah, Nadlifah; Rokhimawan, M Agung; Hanifatunnisa, Hanifatunnisa; Sihono, Sihono; Lesvinanda, Adhelia Shelyn (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine how religious moderation is implemented in the teaching materials and learning methods of the "Professionalism and Leadership" course of the PIAUD UIN Sunan Kalijaga study program. This study is classified as a field study with a qualitative approach. Data were obtained through interviews, observations, and documentation of PIAUD lecturers and students. Analysis was carried out by reducing data and drawing conclusions, while the validity of the data was tested through credibility, transferability, dependability, and confirmation. The results showed that the value of religious moderation is reflected in the teaching materials and learning methods of the Professionalism and Leadership course. The RPS contains themes such as ethics, professionalism, and character development that are in line with the values of justice, tolerance, and balance. Discussion methods, questions and answers, and group assignments encourage an open, critical, and respectful attitude. All of this equips students as prospective moderate and inclusive educators.